Pre-transplant whole blood transcriptomic profiling identifies mRNAs linked to cirrhosis-associated immune dysfunction as candidate predictors of clinical outcomes after liver transplantation: an exploratory study - Marie-Charlotte Delignette; Estelle Peronnet; Arnaud Riff; Teresa Antonini; Maxime Bodinier; Elisabeth Cerrato; Solène Pantel; Elsa Coz; Xavier Muller; Guillaume Rossignol; Jean-Yves Mabrut; Jérôme Dumortier; et al. (Transplant International, 2026)
Cirrhosis-associated immune dysfunction (CAID) contributes to poor outcomes after liver transplantation (LT), but pre-transplant immune predictors remain insufficiently defined. We investigated whether pre-transplant whole blood transcriptomic profiling was associated with post-LT outcomes in this exploratory ancillary study of the prospective EDMONHG cohort. Transcriptomic analysis of 26 immune-related genes was performed on 97 LT recipients. PCA and volcano plots identified candidate biomarkers; associations with outcomes were assessed using ROC analyses and Kaplan-Meier estimates with cohort medians as thresholds. PC1 (43.5% of variance) decreased progressively from cACLD to ALF (p < 0.001) and was lower in post-LT infected patients (p = 0.044). Within the first month, 34 patients (35%) developed infections; 7 (7.2%) died within 1 year. Three genes met predefined exploratory criteria (q < 0.10, AUC > 0.65) for infections: GNLY and IL7R were downregulated and IL10 upregulated. Low GNLY or high IL10 expression was associated with reduced 30-day infection-free survival (p = 0.019 and p = 0.013). CIITA, IL10, CD177 and S100A9 showed associations with one-year survival, though results should be treated as exploratory given the limited number of events. Pre-transplant transcriptomics captures CAID severity and identifies candidate gene signatures associated with post-LT outcomes. These hypothesis-generating findings warrant validation in larger multicenter cohorts.